A Generalized Integral Inequality on Discontinuous Functions in the Teaching of Mathematical Analysis - Zheng, Bin (IJRDO- Journal of Educational Research, 2018)
In this paper, we research a generalized integral inequality with two independent variables for discontinuous function in the teaching of the Mathematical Analysis course. The inequality provides an explicit bound for solutions of certain integral equations. The obtained result extends some existing results in the literature.